A general-purpose analytical model for reconstructing the thunderstorm outflows of travelling downbursts immersed in ABL flows. Issue 207 (December 2020) - Xhelaj, Andi; Burlando, Massimiliano; Solari, Giovanni
Abstract: A "downburst" is defined as a diverging wind system that occurs when a strong downdraft induces an outflow of damaging winds on or near the ground. Severe wind damage in many parts of the world are often due to thunderstorm outflows and their knowledge is therefore relevant for structural safety and design wind speed evaluation. Nevertheless, there is not yet a shared model for thunderstorm outflows and their actions on structures. In this paper, an analytical model that simulates the horizontal mean wind velocity originated from a travelling downburst is proposed. The horizontal wind velocity is expressed as the vector summation of three independent components: the stationary radial velocity generated by an impinging jet over a flat surface, the downdraft translating velocity, which corresponds to the parent cloud motion, and the boundary layer background wind field at the surface where the downburst is immersed. A parametric analysis is also developed and coupled with the analytical model aiming to investigate two observed downburst events and extract their main parameters – e.g. downdraft diameter, touch-down position, translating downdraft speed and direction, intensity and decay period - in order to reconstruct the space-time evolution of these events and validate the model itself. Highlights: An analytical model is developed to simulate thunderstorm outflows. Downburst parameters are estimated through a parametric analysis. Two real-scale thunderstorm outflows are simulated.